The Enlightenment of Dewey’s Educational Theory on English Classroom Teaching in Primary and Secondary Schools - Yuan, Fuli (Journal of Theory and Practice of Contemporary Education, 2023)
Currently, with the continuous development of education globalization, information technology, and internationalization, English classroom teaching in primary and secondary schools is facing many problems and difficulties, such as insufficient preparation of teachers for English classroom teaching activities, single classroom interaction with students, and neglect of students' subjectivity and hierarchical differences. Dewey's educational theory has had a profound and lasting impact on the development of China's education industry. Combining the current situation of English classroom teaching, discussing Dewey's educational theory is of great significance for improving the English education model in primary and secondary schools and achieving the goal of English classroom education in primary and secondary schools.